O princípio da credibilidade na seleção da Informação Mediática - Serra, Paulo (2024)
The most recent developments in mediatic communication have pointed out credibility as a central problem. Seen by the classic rethoric as the main persuasion way, credibility has been revealed nowadays as an essencial matter in the selection of information by a receptor which faces a more and more excessive mediatic information, both in qualitative and quantitative points of view. The question is to know what are the criteria that allow the receptor to infer about the credibility of information he needs or wants. We believe these criteria have essencially been faked in the classic rethoric, thus, suffering the necessary adaptations, they started to constitute the credibility dispositive of the "informative" and "news" traditional mediatic organizations; a dispositive that, through a mainly reflexive process, is to be exported to the Web, tending to transform it in an information in a so said "objective" and impartial" information that excludes all others kinds of information.